Effects of EDTA feeding on survival and development of European corn borer larvae - Knight, Mylah; Cooper, Anastasia; Silver, Kristopher (My University, 2017)
RNA interference (RNAi) is a process that uses double-stranded RNA (dsRNA) to target and suppress the expression of specific genes (Zhang et al., 2010). It is a powerful tool that has been used to understand the function of many genes and has great potential to control insect pests. However, differences in sensitivity to RNAi among insects have limited the use of RNAi (Kim et al., 2015). In some insects, such as European corn borer (ECB), RNAi efficiency is limited by degradation of dsRNA in insect gut. Strategies to overcome this limitation are necessary. Some studies have suggested that high temperatures or treatment with EDTA can inhibit nuclease activity (Garbutt et al., 2014), however the effects of treatment of insects with EDTA are unknown. The objective of this study was to determine if feeding different concentrations of EDTA to ECB larvae will have any effect on larval survival, weight, or development. Our results showed that neither 6 nor 10 mM EDTA had any significant effect on larval survival or development from 2nd instar to 3rd instar larvae. In contrast, average larval weight was suppressed by treatment with 10 mM EDTA. These data show that larvae can be safely treated with up to 6 mM EDTA without adverse effects on development or larval survival, suggesting that 6 mM EDTA can be used in future experiments to test the ability of EDTA to inhibit nuclease activity in ECB gut and possibly improve RNAi efficiency.